1) 5a-2b+3b-4a-1 a= -1 b=2 (2)7x²-3x²-2x-2x²=
1个回答
) 5a-2b+3b-4a-1 a= -1 b=2
解=a+b
=把a=-1,b=2代入得;
=-1+2
=1
相关问题
(5a-4b)^2-(5a-4b)(3a-2b) (2x-1)(2x+1)(4x^2-1)
(2a+3b)(-2a+3b) (x-1)(x+3)-x(x+5)-8 (2a-b+1)(b+2a-1) (3a-2b+
求值:①7x^2-3x^2-2x-2x^2+5+6x,其中x=-2②5a-2b+3b-4a-1,其中a=-1,b=2
1.b/a-b+1/a 2.(a-2b)平方/ab-(a+2b)平方/ab 3.5-3x/x-2+1-x/2-x 4.x
(1)2X+3)/(X-1)(X+2)=A/x-4+B/x+2,那A-B= (2)3X2-X=1,则6X3+7X2-5X
计算:1.(2x+7)(3x-4)+(3x+5)(3-2x)2.[(a-3b)(a+3b)-(3b-a)²]÷
已知A=3x-5x^2-7 ,B=x^3+x-3x^2 (1)求A-[3B-2(A-B)] (2)若x=-1.5(-3/
计算:-3x+(x-1)-(3x-3)= 2(a-2)-3(a+1)= -(5a-4b)+2(a-2b)=
3a+2b-5a-b其中a=-2,b=1 3x-4x的平方+7-3x+2x的平方+1其中x=-3
1.5a+3[2b-3(a-b+2c)-(b+c)] 2.4x²-[2x-(x²-2x+3)-2(x